2013
DOI: 10.1016/j.conb.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Neural control of sexually dimorphic behaviors

Abstract: All sexually reproducing animals exhibit gender differences in behavior. Such sexual dimorphisms in behavior are most obvious in stereotyped displays that enhance reproductive success such as mating, aggression, and parental care. Sexually dimorphic behaviors are a consequence of a sexually differentiated nervous system, and recent studies in fruit flies and mice reveal novel insights into the neural mechanisms that control these behaviors. In the main, these include a diverse array of novel sex differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 88 publications
0
52
0
Order By: Relevance
“…Pheromone-responsive circuits in the brain include subsets of sexually dimorphic nuclei expressing sex-steroid receptors thought to be primarily responsible for changes in sex-specific behavior (Manoli et al, 2013; Morris et al, 2004; Yang and Shah, 2014). However, the formal possibility that behavior regulation also occurs by altering signaling in the pheromone-detecting sensory neurons has not been previously evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Pheromone-responsive circuits in the brain include subsets of sexually dimorphic nuclei expressing sex-steroid receptors thought to be primarily responsible for changes in sex-specific behavior (Manoli et al, 2013; Morris et al, 2004; Yang and Shah, 2014). However, the formal possibility that behavior regulation also occurs by altering signaling in the pheromone-detecting sensory neurons has not been previously evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…As the hypothalamus contains many sexually dimorphic neuronal populations (Manoli et al, 2013; Simerly 2002), we quantified neuronal changes in both sexes. In the Arc, orexigenic neurons are characterized by their co-expression of Agrp and Npy , whereas anorexigenic neurons are characterized by their expression of Pomc and Cart (Broberger, 1999; Horvath et al, 1997; Ovejso et al, 2001); both populations are Dbx1 -derived (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A change in neonatal odor valence from aversion to attraction has been attributed to the ordered release of pregnancy hormones, which in turn, cause a re-routing of amygdala outputs. Sex hormone signaling also shapes the architecture and function of olfactory circuits during a perinatal critical period and at puberty [121]. Testosterone produced during a perinatal surge is converted locally in the brain into estradiol, which perhaps counterintuitively, functions as an organizing signal to masculinize neural circuits.…”
Section: Odor Valence In Micementioning
confidence: 99%